Pengetahuan Perpajakan, Pemahaman Peraturan Perpajakan, Kesadaran dan Kepatuhan Wajib Pajak E-Commerce - Dewi, Ni Putu Ana Kusuma; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2023)
The existence of E-commerce can help companies to expand market share at the national level and expand business across countries. This fact provides new opportunities for e-commerce as a tax object target. The research aims to examine the influence of tax knowledge, understanding of tax regulations, taxpayer awareness on E-commerce taxpayer compliance conducted in the South Denpasar area. The sampling method used purposive sampling method. The sample in this study is 159 e-commerce business people spread across South Denpasar. Data is processed using multiple linear regression. The results of the study show that knowledge of taxation, understanding of tax regulations, awareness of taxpayers has a positive effect on taxpayer compliance in E-commerce in South Denpasar. Keywords: Tax Knowledge; Understanding of Tax Regulations; Taxpayer Awareness; Taxpayer Compliance